Preoperative gadoxetic acid–enhanced MRI for predicting microvascular invasion in patients with single hepatocellular carcinoma - Lee, Sunyoung; Kim, Seong Hyun; Lee, Ji Eun; Sinn, Dong Hyun; Park, Cheol Keun (Journal of hepatology, 2017)
[Display omitted] •MR imaging features were independent predictors for microvascular invasion of HCC.•MR imaging findings can be used as a biomarker for microvascular invasion of HCC.•A combination of MR imaging findings is associated with early recurrence of HCC. This study aimed to identify preoperative magnetic resonance (MR) imaging biomarkers for predicting microvascular invasion (MVI), to determine their diagnostic performance and to evaluate whether they are associated with early recurrence after surgery for single hepatocellular carcinoma (HCC). The study included 197 patients with surgically resected HCC (≤5cm) who underwent preoperative gadoxetic acid–enhanced MR imaging. Significant MR imaging findings for predicting MVI were identified by univariate and multivariate analyses. Early recurrence rates (<2years) were analyzed with respect to significant imaging findings for predicting MVI. Three MR imaging features were independently associated with MVI: arterial peritumoral enhancement (odds ratio [OR]=5.184; 95% confidence interval [CI]: 2.228, 12.063; p<0.001), non-smooth tumor margin (OR=3.555; 95% CI: 1.627, 7.769; p=0.001), and peritumoral hypointensity on hepatobiliary phase (HBP) (OR=4.705; 95% CI: 1.671, 13.246; p=0.003). When two of three findings were combined, the specificity was 92.5% (124/134). When all three findings were satisfied, the specificity was 99.3% (133/134). Early recurrence rates were significantly higher in patients with single HCC, with two or three significant MR imaging findings, compared to those with none (27.9% vs. 12.6%, respectively, p=0.030). A combination of two or more of the following; arterial peritumoral enhancement, non-smooth tumor margin, and peritumoral hypointensity on HBP, can be used as a preoperative imaging biomarker for predicting MVI, with specificity >90%, and is associated with early recurrence after surgery of single HCC. Lay summary: A combination of two or more of the following; arterial peritumoral enhancement, non-smooth tumor margin, and peritumoral hypointensity on hepatobiliary phase, can be used as a preoperative imaging biomarker for predicting microvascular invasion, with specificity >90%, and is associated with early recurrence after curative resection of single HCC.